The Influence of Auxin, Cacodylic Acid, and Amitrole on the Abscission of Petiole Explants - Burt, G. W. (1971)
The influence of indoleacetic acid, cacodylic acid (hydroxy-dimethylarsine oxide), and amitrole (3-amino-1,2,4-triazole) on the petiole explant abscission rate was studied in three species. Indoleacetic acid increased the abscission rate in both bean (Phaseolus vulgaris L. var. Red Kidney) and Coleus (Coleus blumei Benth) at 10(−3) and 10(−4)m but had no effect on abscission in privet (Ligustrum ovalifolium). Cacodylic acid was found to stimulate abscission in explants of beans and privet, but not in Coleus. Amitrole did not stimulate abscission under any circumstance tested. In no case was the abscission rate dependent on the time at which any of the chemicals was applied. These data do not support the two-phase response of explants to applied auxin.